2018
DOI: 10.1002/ccr3.1880
|View full text |Cite
|
Sign up to set email alerts
|

Complete metabolic response of metastatic castration‐resistant neuroendocrine carcinoma of the prostate after treatment with RRx‐001 and reintroduced platinum doublets

Abstract: Key Clinical MessagePresented herein is the case of a heavily pretreated patient with high‐grade neuroendocrine prostate cancer that achieved a complete metabolic response on platinum‐based chemotherapy after treatment with the dual CD‐47 and SIRP‐α inhibitor, RRx‐001, in a Phase II clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Even though 81% of prostate cancers are pathologically organ-confined at time of diagnosis. 10 After diagnosis prostate cancer can metastasized to other organs of the body if the treatment is not effective. 3-BPA is a known chemotherapeutic drug by itself.…”
Section: Increased Incidence Of Prostate Cancermentioning
confidence: 99%
“…Even though 81% of prostate cancers are pathologically organ-confined at time of diagnosis. 10 After diagnosis prostate cancer can metastasized to other organs of the body if the treatment is not effective. 3-BPA is a known chemotherapeutic drug by itself.…”
Section: Increased Incidence Of Prostate Cancermentioning
confidence: 99%
“…In clinical trials RRx-001 has been shown to be biologically active at safe doses in target populations (those with advanced metastatic solid organ tumours), and to be a potent generator of reactive nitrogen and oxygen species in vivo 244,245 . A number of case reports and Phase I trials against metastatic or end-stage Non-Small and Small Cell Lung Cancers, squamous tumours, prostate cancers, and melanomas have indicated that RRx-001 may have beneficial effects when combined with previously exhausted chemo-or radio-therapeutic strategies [246][247][248][249][250][251] .…”
Section: Rrx-001mentioning
confidence: 99%